2020
DOI: 10.1155/2020/6967845
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Strengthening Performance of Concrete Beam by Fiber‐Reinforced Polyurea (FRPU) Reinforcement

Abstract: Polyurea coating helps improve the ductility and toughness of structural members. A fiber-reinforced polyurea (FRPU) composite provides high load-carrying capacity and is applied by simply spraying it onto the member surface. Unlike existing reinforcement approaches, the FRPU coating method can prevent the ductility of concrete beams from deteriorating and the concrete surface from debonding. In this study, 20 concrete beams were tested with respect to their load-carrying capacity and flexural ductility using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…This system provides a high load‐bearing capacity and is easily applied by spraying on the surface of the structure and impedes the deterioration of the concrete rebars and the disintegration of the concrete surface. Reinforcement of the concrete specimens with the FRPU to maintain the load capacity and flexural flexibility has been confirmed to some extent after the concrete failure 83 …”
Section: Polyurea Compositesmentioning
confidence: 86%
“…This system provides a high load‐bearing capacity and is easily applied by spraying on the surface of the structure and impedes the deterioration of the concrete rebars and the disintegration of the concrete surface. Reinforcement of the concrete specimens with the FRPU to maintain the load capacity and flexural flexibility has been confirmed to some extent after the concrete failure 83 …”
Section: Polyurea Compositesmentioning
confidence: 86%
“…The initial cracks in all the specimens appeared in the displacement range of 0.2-0.8 mm, as presented in Table 2. FEMA 273 [25] and FEMA 306 [26] reported that a masonry wall subjected to an in-plane load fails by rocking, toe crushing, sliding, and diagonal tension. Diagonal tension and mortar cracks were evident in all the specimens.…”
Section: Failure Modesmentioning
confidence: 99%
“…By modifying the Triantafillou [7] and AC125 [25,26] models, this study proposed formulas to describe the degree of strengthening caused by GFRPU. It is not practical to construct a two-sided reinforcement using GFRPU, and the X-type reinforcement is rarely differentiated from the one-sided reinforcement of the wall when considering the construction and the experimental results.…”
Section: Derivation Of Formula To Describe the Gfrpu Reinforcementmentioning
confidence: 99%
“…Wu et al [19] investigated the reinforcing effect based on the coating thickness and compared the reinforcement effect for nonreinforced and polyurea-reinforced clay brick walls against blast loads. The reinforcement effect on concrete beams and columns reinforced by glass fiber-reinforced polyurea (GFRPU) mixed with milled glass fiber to improve the tensile strength of polyurea [20][21][22][23] was investigated. The authors reported that GFRPU was effective in enhancing the strength and ductility of structural members.…”
Section: Introductionmentioning
confidence: 99%